Cannabis Liberalization and Adolescent Cannabis Use: A Cross-National Study in 38 Countries - Shi, Yuyan (PLoS One, 2015)
AIMS: To assess the associations between types of cannabis control policies at country level and prevalence of adolescent cannabis use. SETTING, PARTICIPANTS AND DESIGN: Multilevel logistic regressions were performed on 172,894 adolescents 15 year of age who participated in the 2001/2002, 2005/2006, or 2009/2010 cross-sectional Health Behaviour in School-Aged Children (HBSC) survey in 38 European and North American countries. MEASURES: Self-reported cannabis use status was classified into ever use in life time, use in past year, and regular use. Country-level cannabis control policies were categorized into a dichotomous measure (whether or not liberalized) as well as 4 detailed types (full prohibition, depenalization, decriminalization, and partial prohibition). Control variables included individual-level sociodemographic characteristics and country-level economic characteristics. FINDINGS: Considerable intra-class correlations (.15-.19) were found at country level. With respect to the dichotomized cannabis control policy, adolescents were more likely to ever use cannabis (odds ratio (OR) = 1.10, p = .001), use in past year (OR = 1.09, p = .007), and use regularly (OR = 1.26, p = .004). Although boys were substantially more likely to use cannabis, the correlation between cannabis liberalization and cannabis use was smaller in boys than in girls. With respect to detailed types of policies, depenalization was associated with higher odds of past-year use (OR = 1.14, p = .013) and regular use (OR = 1.23, p = .038), and partial prohibition was associated with higher odds of regular use (OR = 2.39, p = .016). The correlation between cannabis liberalization and regular use was only significant after the policy had been introduced for more than 5 years. CONCLUSIONS: Cannabis liberalization with depenalization and partial prohibition policies was associated with higher levels of regular cannabis use among adolescents. The correlations were heterogeneous between genders and between short- and long-terms.